Does the Balance of Power Within a Family Matter? The Case of the Retirement Equity Act - Saku Aura (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper studies within-family decision making regarding investment in income protection for surviving spouses. A change in US pension law (the Retirement Equity Act of 1984) is used as an instrument to derive predictions both from a simple Nash-bargaining model of the household and from the classical single-utility-function model of the household. This law change gave spouses of married pension-plan participants the right to survivor benefits unless they explicitly waived this right. The predictions of the classical model are rejected in favor of the predictions of the Nash-bargaining model in the data.
Keywords: 330